2013
DOI: 10.1021/la401993q
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Study of Chitosan/Polyol-phosphate Systems: Influence of the Polyol Part on the Thermo-Induced Gelation Mechanism

Abstract: Thermo-sensitive gelling systems, like chitosan/polyol-phosphate, are candidates with a high potential for the design of biodegradable drug delivery systems, notably for in situ forming depots. They consist of stable and low viscosity aqueous solutions, liquid at room temperature, which turn into a gel state upon an increase of temperature (e.g., after subcutaneous administration). This technology enables a sustained release of potentially encapsulated active substances. Despite these thermo-gelling solutions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 39 publications
3
55
0
Order By: Relevance
“…On the other hand, the polyol unit is responsible for the thermal sensitivity of the Cs solution. Both the chemical structure and size of the polyol moiety play a significant role in controlling the gelation process [10]. In Figure 1 this gelation mechanism is clearly depicted.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…On the other hand, the polyol unit is responsible for the thermal sensitivity of the Cs solution. Both the chemical structure and size of the polyol moiety play a significant role in controlling the gelation process [10]. In Figure 1 this gelation mechanism is clearly depicted.…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, an interesting research published by Supper et al [10] demonstrated the specific role of the polyol-phosphate molecules on the thermo-physical gelation process. On the one hand, the phosphate moiety neutralizes the charges along the Cs chains up to the physiological pH, keeping them in the solution state at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…G 0 >G 00 indicates the gel state, whereas G 0 <G 00 indicates the sol state of the system. 22,23 The PEG-PLA aqueous system showed the opposite trend. The PEG-PLA formed a gel with a modulus of about 75 Pa at 10 C, which turned into a sol as the temperature increased.…”
Section: Articlementioning
confidence: 98%
“…Chitosan (GS) is an amino-polysaccharide and a natural biodegradable cationic polymer that has recently attracted much interest in studies and clinical applications; chitosan exhibits excellent biocompatibility, biodegradability, anti-microbial activity, wound healing ability, low immunogenicity, low cost, cell growth promotion, and osteo-conduction properties [1][2][3]. Chitosan is soluble in acidic solution because of the electrostatic repulsion among the polymer chains.…”
Section: Introductionmentioning
confidence: 99%